2018
DOI: 10.1136/jmedgenet-2018-105440
|View full text |Cite
|
Sign up to set email alerts
|

Global microarray profiling identifiedhsa_circ_0064428as a potential immune-associated prognosis biomarker for hepatocellular carcinoma

Abstract: These findings together imply that could be considered as a potential HCC prognosis biomarker. Future in-depth research is required to further illustrate the involvement of in HCC tumourigenesis and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…With the rapid progression and wide application of high-throughput sequencing and microarray, the expression pattern of circRNAs in various human diseases are increasingly reported, and the dysregulated expressions of circRNAs are shown to contribute to the pathogenesis of various cancers [7,[9][10][11][14][15][16][17][18][19]. For instance, in hepatitis B-related HCC, 189 upregulated circRNAs and 37 downregulated circRNAs were found by circRNA microarray, and circRNA_100,338 is further validated to be associated with metastatic progression by acting as an endogenous sponge for miR-141-3p [7].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid progression and wide application of high-throughput sequencing and microarray, the expression pattern of circRNAs in various human diseases are increasingly reported, and the dysregulated expressions of circRNAs are shown to contribute to the pathogenesis of various cancers [7,[9][10][11][14][15][16][17][18][19]. For instance, in hepatitis B-related HCC, 189 upregulated circRNAs and 37 downregulated circRNAs were found by circRNA microarray, and circRNA_100,338 is further validated to be associated with metastatic progression by acting as an endogenous sponge for miR-141-3p [7].…”
Section: Discussionmentioning
confidence: 99%
“…Through validation assays, low hsa_circ_ 0064428 expression was found in HCC patients with high TILs and exhibited close correlation with overall survival, tumour size and metastasis in patients with HCC [101]. It can be concluded that hsa_circ_0064428 functioned as a novel immune-associated prognostic biomarker for HCC patients [101]. Programmed death-ligand 1/programmed death-1 (PD-L1/PD-1), as key immune checkpoints, can suppress the activation of T lymphocytes and increase the immune tolerance of tumour cells, thereby achieving tumour immune escape [102][103][104].…”
Section: Circrnas and Lymphocytesmentioning
confidence: 98%
“…Then, Weng et al performed global circRNA microarray between plasma of HCC patients with high TILs and low TILs [101]. Through validation assays, low hsa_circ_ 0064428 expression was found in HCC patients with high TILs and exhibited close correlation with overall survival, tumour size and metastasis in patients with HCC [101]. It can be concluded that hsa_circ_0064428 functioned as a novel immune-associated prognostic biomarker for HCC patients [101].…”
Section: Circrnas and Lymphocytesmentioning
confidence: 99%
“…A relatively shorter CAR-T cell persistence provides an opportunity to avoid serious side effects such as cytokine storm and on-target off-tumour toxicity. Weng et al 31 found that hsa_circ_0064428 could be recognised as a potential immune-associated prognosis biomarker for HCC. In a review article, Xia et al 32 introduced applications and advances of CRISPR-Cas9 in cancer immunotherapy.…”
mentioning
confidence: 99%